Metformin treatment and risk of diabetic peripheral neuropathy in patients with type 2 diabetes mellitus in Beijing, China - Ruotong Yang; Huan Yu; Junhui Wu; Junhui Wu; Hongbo Chen; Hongbo Chen; Mengying Wang; Siyue Wang; Xueying Qin; Tao Wu; Yiqun Wu; Yonghua Hu; et al. (Frontiers in Endocrinology, 2023)
BackgroundMetformin treatment is associated with vitamin B12 deficiency, which is a risk factor for neuropathy. However, few studies have examined the relationship between metformin treatment and diabetic peripheral neuropathy (DPN), and the available findings are contradictory. We aimed to assess whether metformin treatment is associated with DPN in patients with type 2 diabetes mellitus (T2DM) in Beijing, China.MethodsAll patients with newly diagnosed T2DM between January 2010 and September 2012 in the Medical Claim Data for Employees database were included. Metformin treatment was defined as any record of metformin prescription. The average daily dose of metformin during follow-up was calculated. DPN was defined as DPN admissions occurring after a diagnosis of T2DM in the database. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated using Cox proportional hazards models.ResultsAmong 49,705 T2DM patients, 1,933 DPN events were recorded during a median follow-up of 6.36 years. The crude incidence rates were 7.12 and 3.91 per 1000 person-years for patients treated with metformin (N=37,052) versus those not treated (N=12,653). Patients treated with metformin had an 84% increased risk of DPN compared with patients not using metformin (HR, 1.84; 95% CI, 1.62, 2.10). The daily dose was positively associated with DPN risk (HR, 1.48; 95% CI, 1.46, 1.51; P for trend <0.001). The risk of DPN was 1.53-fold (1.30, 1.81) and 4.31-fold (3.76, 4.94) higher in patients with daily doses of 1.0-2.0 g and >2.0 g, respectively, than in patients who did not receive treatment. Patients aged less than 60 years had a higher risk of DPN (P<0.05 for interaction test). Among patients taking vitamin B12 at baseline, there was no increased risk of DPN in the metformin group (1.92: 0.79, 4.69).ConclusionsIn Chinese patients with T2DM, metformin treatment was associated with an increased risk of DPN admission and this risk responds positively to the daily dose of metformin. In particular, metformin use was a major risk factor for DPN in younger patients. Concomitant use of vitamin B12 may avoid the increased risk of DPN associated with metformin use.